The post-Chornobyl library : Ukrainian postmodernism of the 1990s - Hundorova, T. I. (Ukrainian studies (Boston, Mass.), 2019)
"Having exploded on the margins of Europe, Chornobyl marked the end of the Soviet Union and tied the era of postmodernism in Western Europe with nuclear consciousness. The Post-Chornobyl Library in Tamara Hundorova's book becomes a metaphor of a new Ukrainian literature of the 1990s, which emerges out of the Chornobyl nuclear trauma of the 26th of April, 1986. Ukrainian postmodernism turns into a writing of trauma and reflects the collisions of the post-Soviet time as well as the processes of decolonization of the national culture. A carnivalization of the apocalypse is the main paradigm of the post-Chornobyl text, which appeals to "homelessness" and the repetition of "the end of histories." Ironic language game, polymorphism of characters, taboo breaking, and filling in the gaps of national culture testify to the fact that the Ukrainians were liberating themselves from the totalitarian past and entering the society of the spectacle. Along this way, the post-Chornobyl character turns into an ironist, meets with the Other, experiences a split of his or her self, and witnesses a shift of geo-cultural landscapes"--